The Paradox of Quarter-Life Crisis: A Critique of Generational Alienation and Qur'anic Value-Based Solutions - Tomu, Moh. Dandriyandi I. H.; Sahi, Yayan (Jambura Journal Civic Education, 2025)
This study aims to examine the paradox of the Quarter Life Crisis (QLC) as a critique of the alienation of the young generation in the Society 5.0 Era while offering solutions based on Qur'anic values, with a case study in Gorontalo Province. The method used is qualitative with primary, secondary, and tertiary data sources. A survey of 82 respondents revealed that more than 40% experienced high-frequency QLC, which is related to social pressure and the development of digital technology. The three main indicators of QLC include self-identification that is often experienced, dominant worries about career (35.4%), mental health, life goals, and the significant influence of digital technology (89.1%). The qualitative analysis reinforces that digital advances bring new complexities to the lives of the younger generation, while weak spiritual resilience and understanding of religious values exacerbate the condition of QLC. This study reconstructs the verses of the Qur'an and the main interpretations to offer solutions through three important awareness: (1) Cognitive Awareness, (2) Skills Awareness, and (3) Disposition Awareness. This approach emphasises internal transformation that is in line with the principle of amar ma'ruf nahi munkar. Surah Ar-Ra'd verse 11 becomes a strategic foothold, emphasising that changes in external conditions must begin with changes in oneself. Tafsir Al-Mishbah, Al-Qurthubi, and Al-Azhar reinforce the importance of mental attitude, effort, and self-awareness in facing QLC. Thus, spiritual strengthening and character based on Qur'anic values are the key to overcoming the identity crisis and emotional pressure of the younger generation in the Society 5.0 Era.